A quality assessment (physic phytochemical profile) of root of Withania somnifera (L.) Dunal used traditionally for therapeutic purposes in Sri Lanka - Vinotha, S.; Ira, T.; Sri Ranjani, S. (World Ayurveda Foundation, 2012)
Withania somnifera (Linn) Dunal is widely used in the traditional medicinal sys-tem of Sri Lanka. Quality assessment of root of W. somniferous, grown in India has been published [Nasreen and Radha 2011]. However, root of W. somnifera used in preparation of traditional medicines in Jaffna District are mainly purchased from local vendors that import it from India. Therefore, it was important to carry out a Quality assessment of the plant material available in Jaffna to ensure the authenticity of this plant material and to prevent any adulteration, especially when used in the powdered form.